Nicaraguan Pipunculidae (Diptera): new records and description of new species - Rafael, José Albertino; Ale-Rocha, Rosaly (Zootaxa, 2004)
Six hundred and ten Nicaraguan pipunculid specimens were studied. Twenty-three species and eight genera are reported and geographical distribution presented. One species, Tomosvaryella subvirescens (Loew) was previously recorded. Fifteen new distribution records and seven new species are described and illustrated: Elmohardyia nicaraguensis Rafael, Eudorylas maesi Rafael, E. platyapodemalis Rafael, E. subvexus Rafael, E. trichosubepandrialis Rafael, Dasydorylas vulcanus Rafael and Tomosvaryella crassa Ale-Rocha. Three species of Neotropical Eudorylas are transferred to the genus Dasydorylas Skevington: D. eremita (Hardy), n. comb., D. nigellus (Rafael), n. comb., and D. regalis (Curran), n. comb.